Emerging Themes of Regulation at the Golgi - Makowski, Stefanie L. (Curr Opin Cell Biol, 2017)
The Golgi is generally recognized for its central role in the secretory pathway to orchestrate protein post-translational modification and trafficking of proteins and lipids to their final destination. Despite the common view of the Golgi as an inert sorting organelle, emerging data demonstrate that important signaling events occur at the Golgi, including those that regulate the trafficking function of the Golgi. The phosphatidylinositol-4-phosphate/GOLPH3/MYO18A/F-actin complex serves as a hub for signals that regulate Golgi trafficking function. Furthermore, the Golgi is increasingly appreciated for its important role in cell growth and in driving oncogenic transformation, as illuminated by the discovery that GOLPH3 and MYO18A are cancer drivers.